Porphyromonas gingivalis bypasses epithelial barrier and modulates fibroblastic inflammatory response in an in vitro 3D spheroid model. Issue 1 (December 2018) - Bugueno, Isaac; Batool, Fareeha; Keller, Laetitia; Kuchler-Bopp, Sabine; Benkirane-Jessel, Nadia; Huck, Olivier
Abstract Porphyromonas gingivalis -induced inflammatory effects are mostly investigated in monolayer cultured cells. The aim of this study was to develop a 3D spheroid model of gingiva to take into account epithelio-fibroblastic interactions. Human gingival epithelial cells (ECs) and human oral fibroblasts (FBs) were cultured by hanging drop method to generate 3D microtissue (MT) whose structure was analyzed on histological sections and the cell-to-cell interactions were observed by scanning and transmission electron microscopy (SEM and TEM). MTs were infected byP. gingivalis and the impact on cell death (Apaf-1, caspase-3), inflammatory markers (TNF-α, IL-6, IL-8) and extracellular matrix components (Col-IV, E-cadherin, integrin β1) was evaluated by immunohistochemistry and RT-qPCR. Results were compared to those observedin situ in experimental periodontitis and in human gingival biopsies. MTs exhibited a well-defined spatial organization where ECs were organized in an external cellular multilayer, while, FBs constituted the core. The infection of MT demonstrated the ability ofP. gingivalis to bypass the epithelial barrier in order to reach the fibroblastic core and induce disorganization of the spheroid structure. An increased cell death was observed in fibroblastic core. The development of such 3D model may be useful to define the role of EC–FB interactions on periodontal host-immune response and to assess the efficacy of new therapeutics.